مفهوم الأدب الإسلامي عند الأديب محمد حسن بريغش: دراسة وصفية تحليلية = Mafhum al-adab al-Islami 'inda Muhammad Hasan Brighish: Dirasah wasfiyyah tahliliyyah - Zubir, Badri Najib; Safian, Nursafira (International Islamic University Malaysia, 2013)
This study aims to discuss the concept of Islamic Literature of the writer Muhammad Hasan Bereghish by analysing his personal views and understanding found in his various books. It also aims to give a general account on his thought and highlight his contributions to the conceptualization of Islamic literature. The study concludes that the characteristics of Islamic literature found in his works cannot be the standards to determine how committed is the literature to Islamic requirements as they are merely general characteristics of literature. It is not enough for him that these characteristics are not conflicting with the Islamic literature as there must be also the element of inclination to Islam and the element of propagation to Allah. Bereghish, in addition to that insisted on the strong attachment between the Muslim writer and the Islamic literature. This attachment however, is not restricted to the fact that the writer is a Muslim in name since he must also be a committed Muslim who abides by the Islamic way of life.